Dietary α-Linolenic Acid-Rich Flaxseed Oil Exerts Beneficial Effects on Polycystic Ovary Syndrome Through Sex Steroid Hormones—Microbiota—Inflammation Axis in Rats - Wang, Ting; Sha, Liping; Li, Yiwei; Zhu, Lili; Wang, Zhen; Li, Ke; Lu, Haixia; Bao, Ting; Guo, Li; Zhang, Xiaoxia; Wang, Hao (Frontiers in Endocrinology, 2020)
Polycystic ovary syndrome (PCOS) represents a common endocrine-metabolic disorder disease with a chronic low-grade inflammation and alteration of intestinal flora. Serving as functional food, flaxseed oil (FO), rich in plant-derived ɑ-linolenic acid (ALA) of omega-3 polyunsaturated fatty acids (PUFAs), has been proven to benefit for chronic metabolic diseases. However, the exact role of dietary FO on PCOS remains largely unclear. In the present study, six-week-old female Sprague-dawley (SD) rats were randomly divided into 4 groups (8 rats/group), including (a) pair-fed (PF) control (CON) group (PF/CON); (b) FO-fed CON group (FO/CON); (c) PF with letrozole-induced PCOS model (MOD) group (PF/MOD); (d) FO-fed MOD group (FO/MOD). All rats were fed a standard diet. After 3 weeks of modeling and subsequent 8 weeks of treatment, rats in diverse groups were euthanized and associated indications were investigated. The results showed that dietary FO ameliorated the disorder of estrous cycle and ovarian morphology. In parallel, dietary FO improved sex steroids hormones disturbance (LH/FSH, E2, T, PROG), body weights (BWs), dyslipidemia and insulin resistance. Moreover, FO treatment suppressed plasma and ovary inflammatory interleukin (IL)-1β, IL-6, IL-10, IL-17A, tumor necrosis factor-α (TNF-α) and monocyte chemoattractant protein-1 (MCP-1). Additionally, FO intervention significantly modulated the composition of gut microbiota and vaginal microbiota (VMB) by increasing the abundances of Allobaculum, Lactobacillus, Butyrivibrio, Desulfovibrio, Bifidobacterium, Faecalibacterium, Parabacteroides as well as decreasing Actinobacteria, Bacteroides, Proteobacteria, Streptococcus, the ratio of Firmicutes/Bacteroidetes (F/B). A decrease in plasma lipopolysaccharide (LPS) level and an increase in short chain fatty acids (SCFAs) including acetic acid, propionic acid, butyric acid and pentanoic acid were determined after dietary FO supplementation. Correlation analysis revealed close relationships among sex steroids hormnones, inflammation and gut/vaginal microbiota. Collectively, this study demonstrated that dietary FO ameliorated PCOS through sex steroids hormones-microbiota-inflammation axis in rats, which may contribute to the understanding of pathogenesis and potentially serving as an inexpensive intervention in the control of PCOS.